Cerpen Tiga Paragraf sebagai Strategi Pentigrafis Katolik dalam Mewartakan Injil Saat Pandemi Covid 19 - Ardi Wina Saputra; Agustinus Indradi; Blasius Perang (Aksara, 2023)
The problem of this research is to look at the Indonesian Catholic pentigraphic strategy in proclaiming the gospel through a three-paragraph short story. The purpose of this study is to analyze the pentigraphic strategy of Indonesian Catholics in evangelizing during the Covid-19 pandemic. This research method is qualitative research. The data sources in this study were five Catholic pentigraphers with various backgrounds, and pentigraph works from the five informants. Data were analyzed by social practice analysis from Pierre Bourdieu and text analysis. This research produced findings in the form of Catholic pentigraphical forms in preaching the gospel during a pandemic and Catholic pentigraphical forms. The main strategic manifestations of Catholic pentigraphers are (1) having the habit of reading and writing, (2) having an important role in the church and society, and (3) conveying the message of the Bible implicitly through fictional prose. The pentigraph forms made by Catholic pentigraphers have special meanings, namely (a) responding to social reality, (b) having the message of the Bible, and (c) conveying the meaning of the Bible implicitly. AbstrakMasalah penelitian ini adalah melihat strategi pentigrafis Katolik Indonesia dalam mewartakan injil melalui cerpen tiga paragraf. Tujuan penelitian ini, yaitu untuk menganalisis strategi pentigrafis Katolik Indonesia dalam mewartakan injil saat pandemi Covid-19. Metode penelitian ini adalah metode kualitatif. Sumber data dalam penelitian ini, yaitu lima pentigrafis Katolik dengan beragam latar belakang dan karya pentigraf dari kelima narasumber tersebut. Data dianalisis dengan analisis praktik sosial dari Pierre Bourdieu dan analisis teks. Penelitian ini menghasilkan temuan berupa wujud strategi pentigrafis Katolik dalam mewartakan injil saat pandemi dan bentuk pentigrafis Katolik. Wujud strategi utama yang dimiliki oleh pentigrafis Katolik, yaitu (1) memiliki kebiasaan membaca dan menulis, (2) memiliki peran penting dalam lingkungan gereja dan masyarakat, serta (3) menyampaikan pesan Injil secara tersirat melalui prosa fiksi. Bentuk pentigraf yang dibuat oleh pentigrafis Katolik memiliki makna khusus, yaitu (a) merespons realitas sosial, (b) memiliki pesan Injil, dan (c) menyampaikan makna Injil secara tersirat.